Exploring the potential mechanisms of the Prunus mume-Prunella vulgaris herb pair in treating endometrial polyps based on network pharmacology and molecular docking - Wen Yan Zhang; Yuan Yuan; Li Fan; Guang Rong Huang; Shu Yu Pan; Jing Xiao (Molecular Genetics and Genomics, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

DA-MOT: a directed-angle-aware multi-object tracking framework for dairy cows - Tonghui Wu; Rong Wang; Haiyan Song; Zhiyong Zhang; Qifeng Li; Zhaoyang Wang; Yan Shi; Ronghua Gao (Computers and Electronics in Agriculture, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

The needs-solution-prototype-validation model: A feasibility study of nurse-led interdisciplinary collaboration in medical device innovation - Xiaodong Zhang; Fengli Wang; Aiying Gu; Haoyuan Li; Wei Wang; Yongchao Huo; Rong Xu; Yuanfeng Xue; Guohong Li; Yan Geng (Next Research, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Heat stress modulates the size-dependent effects of aminated polystyrene particles on a marine diatom - Ting-Ting Xu; Zhen-Liang Li; Zhi-Yan Wang; Yu-Han Xie; Heng-Xiang Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2026)

Electrostatic-field-driven synergistic regulation of molecular conformation and mesostructure enables stable Na+ transport in 12 μm PVDF-HFP-based electrolytes - Jiaze Li; Rong Yang; Xiaobin Li; Aoyi Jiang; Xin Dong; Hongyu Shang; Yinglin Yan; Hyun Woo Kim; Jou-Hyeon Ahn (Chemical Engineering Journal, 2026)

Indigenous beneficial microbes contribute to pathogen inhibition in Chinese yam continuously cropped soil - Huanhuan Cheng; Yifan Cao; Paidamoyo Mataranyika; Ziyi Yuan; Yan Wang; Jian Yang; Luqi Huang; Zongzhuan Shen; Qirong Shen; Rong Li (Applied Soil Ecology, 2026)

Morphology and Phylogeny of Hyalinostachys dehongensis sp. nov., a Bambusicolous Species From Yunnan Province, China - Yu‐Rong Yan; Li‐Su Han; Gang‐Ya Xu; Samantha C. Karunarathna; Nakarin Suwannarach; Jaturong Kumla; A. N. W. Sumedha Thushari; Sajad Ali; Dong‐Qin Dai; Saowaluck Tibpromma (New Zealand Journal of Botany, 2026)
China has abundant bamboo resources, among which Yunnan Province is one of the regions with the greatest number of species. The unique natural and geographic advantages provide an excellent environment for fungal growth. This study collected and isolated saprobic hyphomycetes associated with dead bamboo in Yunnan Province, China. Based on detailed morphological comparisons and multi‐locus phylogenetic analyses of combined LSU, ITS, tef 1‐ α , rpb 2, tub 2, and cmdA sequence data, the new isolates are introduced here as a novel species, Hyalinostachys dehongensis in the family Stachybotryaceae of Ascomycota. A complete description, morphological illustrations, and phylogenetic analysis results for the new species are provided. In addition, this species is introduced here as the second species since this genus was introduced in 2020.

Phosphorus limitation and manganese toxicity induced by high nitrogen inputs suppress plant biomass - Jiapu Li; Xuebin Yan; Jordi Sardans; Josep Peñuelas; Shiting Hong; Peng Wang; Pinwei Zhang; Rong Song; Yanwen Zhao; Yong Li; Hui Guo (Plant and Soil, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Burkholderia cepacia NB-13: Biocontrol efficacy and medium-driven metabolic regulation - Zhou Yin; Xiaoqin Li; He Guan; Dindi Tu; Xingyi Luo; Wancheng Hu; Fanqian Zhou; Menglong Li; Shulin Liu; Hui Li; Rong Song; Kailin Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

The dual role of H2 in a hydrogen-rich atmosphere: mechanisms of coke dissolution loss inhibition and strength enhancement - Jialong Yao; An Li; Rong Ge; Jingchong Yan; Zhanku Li; Weidong Zhang; Zhicai Wang; Zhiping Lei; Shibiao Ren; Hengfu Shui (Fuel, 2026)

Acquisitive, diverse tree stands resist vine invasion via contrasting temporal effects on crown volume and herb cover - Li Zhang; Liting Zheng; Marc W. Cadotte; Charles A. Nock; Baiyu Yang; Zhiming Hu; Ciliang Zhao; Wen-Hui You; En-Rong Yan (Forest Ecology and Management, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Optimizing lipid retention for anaerobic membrane bioreactors treating food waste: Balancing methane enhancement and membrane fouling control - Luwei Yan; Shuangquan Zhao; Yu Xi; Yaqian Liu; Yuxin Xiao; Zhen Lei; Qian Li; Rong Chen (Bioresource Technology, 2026)

Refractory Dermatophytosis Caused by Trichophyton indotineae: A Case Series Highlighting Antifungal Resistance and Management Challenges - Yubo Ma; Rong Yan; Yakun Shao; Chunying Xiao; Tianshuo Zhao; Xingyu Li; Gang Wang; Chunying Li; Yinggai Song; Meng Fu; Yanyang Guo (Mycopathologia, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Microbial lifestyles driven by C: N stoichiometric imbalance govern responses of carbon metabolism to nitrogen addition - Bo Kang; Rong Huang; Xun Yan; Linkang Chen; Shanghong Chen; Youlin Luo; Xiaoyan Tang; Yingjie Wu; Qi Tao; Qiang Xu; Changquan Wang; Bing Li (Soil Biology and Biochemistry, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

A novel closed-loop path planning algorithm for unmanned surface vessel swarms based on potential field-guided deep Q-learning - Chunhan Zhang; Rong Zhen; Yu Zheng; Yan Zhang; Jialun Liu; Ke Zhang; Chunxu Li (Ocean Engineering, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

6H2L, a novel derivative of bifendate, dually suppresses glycolysis and glutaminolysis in hepatocellular carcinoma via inhibiting YAP stability - Beibei Zhang; Kaixuan Sheng; Yue Yan; Xinlei Wang; Xinning Cheng; Rong Liao; Zhiyi Yang; Mengyi Li; Fan Wang; Qi Qi; Yu Wang; Chenglin Li (Chemico-Biological Interactions, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

Citral-loaded PVA-PVP hydrogel pad: Preparation, physicochemical properties, characterization, and application for blueberry preservation - Haifeng Rong; Wenna Li; Yuxuan Li; Sixu Lin; Runan Zhao; Yufeng Xu; Bingxin Sun; Yunhe Zhang; Xuerui Yan (Food Packaging and Shelf Life, 2026)

Elevated CO2 accelerates mineral-protected organic carbon loss in the upland rhizosphere after paddy drainage - Xun Yan; Zhifan Li; Bo Kang; Tao Li; Linkang Chen; Junwen Zhao; Bing Li; Youlin Luo; Yingjie Wu; Rong Huang; Xiaoyan Tang; Qiang Xu; et al. (CATENA, 2026)

Operational control mechanism and pilot-scale demonstration of integrated fixed-film activated sludge partial nitritation/anammox system - Zibin Luo; Chao Rong; Tianjie Wang; Yu Qin; Jiang Wu; Yan Guo; Yisong Hu; Zhe Kong; Taira Hanaoka; Shinichi Sakemi; Yu-You Li (Bioresource Technology, 2026)

Biological characterization of an avian leukosis virus subgroup J isolate from yunnan indigenous black-bone chickens and generation of its full-length infectious clone - Hongya Yan; Guojun Wang; Rong Zhao; Ke Li; Zhengju Yuan; Wengui Li; Aiguo Xin (Archives of Virology, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

High-resolution point source pollution database boosts SWAT-QUAL2K coupled model for multi-scale nitrogen and phosphorus management - Yang Bi; Yanxin Zhao; Yi Rong; Ningtong Li; Kai Huang; Yan Chen (Journal of Cleaner Production, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

When city lights turn blue: Spectral ALAN exposure, LED lighting, and diabetes prevalence using SDGSAT-1 - Yanqing Xu; Ruoyu Dong; Tingting Li; Sujin Zhang; Yan Liu; Yuchen Li; Kenan Li; Xiaobo Feng; Shuang Rong (Environmental Pollution, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Two new menthane monoterpene derivatives isolated from Hypericum monogynum - Yan-Rong Zeng; Hong-Jin Ban; Jing-Yi Yin; Zhan Feng; Ya-Nan Li; Yan Liu; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry Letters, 2026)

Tarsus-enriched chemosensory proteins in Achelura yunnanensis (Lepidoptera, Zygaenidae) and their interactions with pesticides - Fu-Peng Li; Zi-Hui Liu; Xiao-Rong Xiong; Jin-Lan Zhang; Hai-Yan Xiao; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Bioinspired interfacial anchoring enables durable ultra-black photothermal coatings based on silica-coated carbon nanotubes - Jian Li; Yan Wang; Xiaolong Wu; Chao Li; De-Rong Sun; Peng Wang; Zimu Li; Xue-Qing Liu (Chemical Engineering Journal, 2026)

Effects of recovered exogenous nitrogen addition on pilot-scale single-cell protein production from soybean soaking water - Hui Xu; Yingqiu Pu; Li Wang; Rong Huang; Yan Zhou (Bioresource Technology, 2026)

Design of sequential strongly convex programming algorithm for reentry trajectory planning - Yutang Li; Di Zhou; Zhen He; Songzhou Li; Siyuan Li; ChaoRan Yan; Rong Huang (Advances in Space Research, 2026)

Salmonella virulence factor sptP activates the NLRP3/Caspase-1 pathway to induce pyroptosis and exacerbate intestinal injury in chicks - Bo Zhang; Ke Li; Hongya Yan; Rong Zhao; Zhenju Yuan; Changrui Xiao; Chengji Yang; Aiguo Xin (Veterinary Microbiology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

A low pH level in ripening pear tissue promotes the growth and pathogenicity of Alternaria alternata by causing ammonia accumulation and alkalization - Meiqi Gao; Rong Li; Yanxia Zhang; Puwei Yan; Xiwang Wang; Yue Xie; Miao Zhang; Yongcai Li (Physiological and Molecular Plant Pathology, 2026)

Experimental evidence on the bitumen role of the metal enrichment in the Erdaokan Ag-Pb-Zn deposit - Shun-Feng Yan; Xiao-Min Zheng; Lin Li; Hai-Yan Zheng; Mao-Wen Yuan; M. Santosh; Sheng-Rong Li (Organic Geochemistry, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

High-performance fiber-based aerogel evaporator for solar desalination and wastewater purification - Yan Liang; Siqi Wu; Yujie Zhao; Ning Liu; Rong Tian; Jianbin Zhang; Yanhua Liu; Dianming Li; Libang Feng (Desalination, 2026)

Lattice distortion-driven electronic engineering of high-entropy alloys for efficient polysulfide catalysis in LiS batteries - Li Zhang; Yan Wang; Bo-Wen Lin; Rong-Rong Liang; Tian-Hui Dang; Zhuo Zhao (Chemical Engineering Journal, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

How human-perceived urban green spaces contribute to mental well-being: a machine learning approach - Enqi Cheng; Yuejing Rong; Yan Yan; Chenxing Wang; Lijie Wang; Yu Zhao; Zetong Wang; Wei Li (Journal of Environmental Management, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Optical diagnostic study on the combustion and soot formation process of nanobubble diesel - Han Wang; Liang Guo; Wanchen Sun; Yuying Yan; Hao Zhang; Miao Yang; Mengqi Jiang; Degang Li; Rong Xuan; Junfeng Zhang; Kaiqi Yang (Fuel, 2026)

Rapid quantitative real-time analysis and visual detection of Escherichia coli in meat by direct PMAxx-VPCR - Jiaqi Cui; Tingting Zhao; Wenjun Song; Huilin Li; Yan Chen; Rong Chen (Food Control, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Cofactor-coupled cytochrome P450 engineering enables high-level biosynthesis of asiatic acid in Saccharomyces cerevisiae - Yuan Zhu; Xiaoguang Yan; Weiguo Li; Yuan Zhong; Jianjun Qiao; Guang-Rong Zhao (Bioresource Technology, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

5-Methoxyflavone inhibits the proliferation of lung adenocarcinoma cells through PI3K/AKT/GSK3β/β-catenin/Cyclin D1 signaling and attenuates chemoresistance and PD-L1 expression - Yan Zhao; Yiwen Cui; Rong Li; Mingyong Li; Zhiwei He; Yingying Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biota occurrence, accumulation, disposition and toxic effect of chlorinated paraffins - Huiming Zhang; Yutong Yang; Mu Zhang; Xue Li; Yan Zhang; Shufen Han; Rong Chen; Jun Yang; Jianyun Zhang (Environmental Geochemistry and Health, 2026)

Organic fertilization improves activities of phosphomonoesters hydrolase in rhizosphere to facilitate phosphorus acquisition in cucumber and accumulates organic phosphorus in soil - Bingshuang Wang; Yuan Wang; Xihe Zhang; Xiaodan Hu; Shujun Li; Yifei Sun; Yang Wang; Yan Sun; Ziwei Dai; Yunsheng Lou; Rong Li; Guohua Xu; et al. (Applied Soil Ecology, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Revealing the role of spin state in catalysis: Medium spin Fe3+ catalyst for lithium‑sulfur batteries - Xin Dong; Rong Yang; Xifei Li; Peiying Li; Yurou Wang; Xuchen Li; Hongyu Shang; Jiaze Li; Chaojiang Fan; Yinglin Yan; Yunhua Xu (Chemical Engineering Journal, 2026)

Performance stability and recovery strategy of pre-denitrification coupled partial nitritation/anammox-hydroxyapatite processes for enhanced organic matter, nitrogen and phosphorus removal from swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Chao Rong; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Bioorganic fertilizers promote plant health by activating phagotrophic protists at different plant growth stages - Zixuan Jiao; Xuhui Deng; Xinyue Yan; Zongzhuan Shen; Qirong Shen; Sai Guo; Rong Li (Applied Soil Ecology, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Side-stream anaerobic membrane bioreactor system for energy-positive sewage treatment - Chao Rong; Weifu Yan; Ying Song; Chunxiao Wang; Zhiguo Yuan; Yu-You Li; Tong Zhang (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Metallurgical organic pollutants assisted source apportionment of mobile heavy metals on artisanal non-ferrous metal processing contamination - Li-Rong Liu; Junyao Yan; Lei Xiang; Ting Liu; Ye Xiao; Wen-Shen Liu; Wen-Jun Wu; Ping Li; Miaoyue Zhang; Yuan-Qing Chao; Ye-Tao Tang; Rong-Liang Qiu (Journal of Hazardous Materials, 2025)

Bi-mediated Z-scheme heterojunction of carbon-rich BiO2-X /Carbon nitride: Enabling a sensitive photoelectrochemical aptasensor for diazinon detection - Quan Shen; Rong Zhi; Song Zhang; Yi Ding; Jing Huang; Yuqi Chen; Keqiang Xu; Pengcheng Yan; Henan Li (Journal of Environmental Chemical Engineering, 2025)

Research on the fungi in dry-cured hams from different regions and exploration of new resources of flavor yeast - Wucong Zhou; Ai Zelin; Zilin Chen; Zhengyang Bao; Minxuan Shi; Chenghan Rong; Shuqing Yan; Xinzhu Zhang; Chunbao Li; Kai Shan (Food Research International, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Faustmann Model Expansion Under Policy Uncertainty: Empirical Evidence from Fujian Province, China - Yan-Zhen Hong; Rong-Huan Zhang; Hai-Jie Kou; Bang-Ni Li (Small-scale Forestry, 2025)

Cholesterol and 24S-OHC Induce Neuronal Apoptosis and Necroptosis, but Not Ferroptosis Despite Elevated Iron Levels - Yinghui Li; Tingbin Xu; Jiahua Yang; Rong Liu; Yan Qu; Jun Wang (Molecular Neurobiology, 2025)

Comprehensive study of W06A7.4 and TMEM144 mediated pathways in aging: insights from Caenorhabditis elegans to human - Li Fang Wang; Xiaorong Liu; Sisi Li; Rong Li; Ran Li; Fengxia Yan; Xi Jing (Molecular Genetics and Genomics, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Development of a Phage‐Display Derived Peptide‐Based Colloidal Gold Strip for Rapid Detection of Enterocytozoon hepatopenaei via Spore Wall Protein Interaction - Jia‐rong Xie; Hao Li; Ben Chen; Yan‐chang Fan; Yu‐hao Gong; Liqun Lu (Journal of Fish Diseases, 2025)
Infection by Enterocytozoon hepatopenaei (EHP) leads to stunted or arrested growth in shrimp, causing significant economic losses in shrimp aquaculture. In this study, the spore wall protein EhSW12 was expressed using a prokaryotic expression system. Subsequently, phage display technology was employed to screen for peptides that interact with EhSW12. A rapid detection method was developed that bypasses the laborious procedure of extracting tissue DNA samples. Instead, enzymatic digestion was used to lyse the spore wall protein present in tissue homogenates, thereby enabling direct detection of EhSW12 via antigen colloidal gold rapid test strips and dot blot assays. The colloidal gold test strips, noted for their convenience and rapidity, satisfy the requirements for on‐site testing, while the dot blot method—with its simple operation—is well suited for high‐throughput sample analysis. Both methods were compared with the national standard qPCR assay. Specificity was validated using various shrimp antigens prepared in the laboratory; the results demonstrated that only the EHP antigen yielded a positive reaction, with no cross‐reaction observed with other common shrimp pathogens (e.g., white spot syndrome virus, decapod iridescent virus and highly pathogenic Vibrio ). Sensitivity tests indicated that the minimum detection limits for the test strip and dot blot methods were, respectively, 7 × 10 6 copies and 5.2 × 10 4 copies. In summary, both methods exhibit strong specificity, high sensitivity, rapid detection speed and operational simplicity—characteristics that make them highly suitable for large‐scale on‐site rapid testing.

Caulerpin suppresses tumor-associated angiogenesis and tumor growth via Hippo signaling in cervical cancer - Guang Yang; Yan Mo; Honghong Rong; Bihui Guo; Qingbing Zha; Hanli Shuai; Minghua Wang; Ping Li (Toxicology and Applied Pharmacology, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Spatial distribution and chemical characteristics of bastnäsite and monazite provide insights into the Bayan Obo deposit, the world's largest rare earth element mineralization - Jin Wang; Lin Li; M. Santosh; Guo-Ying Yan; Jun-Feng Shen; Mao-Wen Yuan; Masroor Alam; Zhao-Jing Wang; Sheng-Rong Li (Lithos, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Layered manure enhances root development via soil hydrothermal optimization in ridge tillage - Bo Kang; Xun Yan; Yingjie Zhang; Rong Huang; Youlin Luo; Qiang Xu; Lihong Han; Changquan Wang; Bing Li (Plant and Soil, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Impact of Ca supplement to the single-stage partial nitritation/anammox-hydroxyapatite process in treating swine manure digestate: deterioration mechanism and recovery strategy - Yunzhi Qian; Shilong He; Chao Rong; Yan Guo; Fuqiang Chen; Junhao Shen; Yu Qin; Yu-You Li (Chemical Engineering Journal, 2025)

Multifunctional integrated separator based on electrospinning structure engineering for high-stability lithium sulfur batteries - Chaojiang Fan; Rong Yang; Bing Chen; Qing Huang; Lingjiang Kou; Jiajia Song; Yong Wang; Teng Wang; Yinglin Yan; Zhongguo Zhao; Kai Jia; Wenhu Li; et al. (Chemical Engineering Journal, 2025)

Porous coordinated polymers/chitosan composite monolith with directional pore structure for highly efficient mono−/multi−/global phosphopeptide enrichment - Rong Li; Yan Wang; Dandan Zhou; Ruizhi Tang; Yangyang Bian; Shujuan Ma; Xingtai Qiu; Zichao Tang; Junjie Ou; Yehua Shen (Carbohydrate Polymers, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Hydrogel pads loaded with essential oil contribute to maintaining blueberry quality after transportation - Yuxuan Li; Haifeng Rong; Sixu Lin; Yaohui Zheng; Ling Yang; Bingxin Sun; Yunhe Zhang; Yufeng Xu; Xuerui Yan (Food Packaging and Shelf Life, 2025)

Nanoplastics under the charge effects: Unveiling the potential threats to amphibian (Rana nigromaculata) growth, intestinal damage and microbial ecology - Peng Fang; Shuzi Ye; Zidie Luo; Rong Guo; Yan Jiang; Lemei Liu; Siwen Li; Fang Xiao (Environmental Pollution, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Oxygen vacancies-mediated the peracetic acid activation to selectively generate 1O2 for water decontamination - Yi Chen; Qian Li; Ruidian Su; Yixuan Gao; Ning An; Yu Rong; Xing Xu; Defang Ma; Yan Wang; Baoyu Gao (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Overexpression of anthocyanin activator LrAN2 improving black goji berry (Lycium ruthenicum) tolerant to cadmium stress - Peiyan Ai; Zhiqiang Wang; Yan Li; Rong Yang; Biao A; Yixin Jia; Yuan Zong; Ying Wang; Shaohua Zeng (Journal of Hazardous Materials, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

The structure and assembly of the epiphytic bacterial community of Saccharina japonica during the field cultivation period - Chun Wang; Shanshan Wang; Zhenhua Wang; Huabin Shao; Xiaojun Rong; Jie Li; Ming Zhu; Yongwei Yan (Algal Research, 2025)

Machine learning-based design, screening, and activity validation of topoisomerase I inhibitors - Ya-Kun Zhang; Jian-Bo Tong; Jia-Le Li; Rong Wang; Yan-Rong Zeng (Molecular Diversity, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Pp07886, a glycoside hydrolase family 5 protein from Pythium porphyrae, is a required virulence factor and induces host disease resistance - Huichao Yang; Zhaolan Mo; Peiwen Weng; Yongwei Yan; Lei Tang; Xiaojun Rong; Jie Li (Algal Research, 2025)

Spatiotemporal analysis of microclimatic and environmental interactions with visualcompensation for thermalcomfort: Case studies in Hangzhou's urban waterfronts - Rong Xia; Zhixing Li; Xiaowen Gao; Siyi Luo; Ruiyin Xiong; Xuzhong Yan (Urban Climate, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Ultra-stable all-solid-state lithium metal batteries facilitated by in-situ LiF-rich single-ion conductor composite polymer electrolytes - Jiaze Li; Rong Yang; Aoyi Jiang; Qianwei Zhang; Xin Dong; Hongyu Shang; Yinglin Yan; Yunhua Xu; Jou-Hyeon Ahn (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Subseasonal Prediction Skill in the CAMS-CSM Subseasonal-to-Seasonal Forecast System - Yuhan Yan; Jingzhi Su; Boqi Liu; Libin Ma; Xinyao Rong; Bo Liu; Yanli Tang; Jian Li (Advances in Atmospheric Sciences, 2025)

Risk Assessment of International Seabed Mining Implementing the Analytic Hierarchy Process - Xinyu Ma; Yejian Wang; Kehong Yang; Jinrong Li; Yan Li; Dongsheng Zhang; Rong Wang; Yinxia Fang (Journal of Marine Science and Engineering, 2025)
The international seabed area (“the Area”) harbors abundant metal mineral resources that are critical to address global metal supply–demand and sustainable development. However, exploitation of mineral resources in the Area faces complex risks spanning politics, economy, technology, science, environment, society, industry, and law. No commercial-scale deep-sea mining operations have been conducted to date. Systematic risk identification and prioritization can inform strategic planning for stakeholders. This study employs literature analysis and an 80-expert questionnaire to identify key risk factors affecting mineral exploitation in the Area. Using the Analytic Hierarchy Process (AHP), we quantitatively assess the relative importance and weightings of these risks. Our results indicate that Level 1 risk groups prioritize (1) policy and public opinion risk, (2) extended continental shelf (ECS) delineation risk, (3) high sea marine protected areas (HSMPAs) establishment risk, and (4) mining area economic value risk. The five most critical Level 2 risk factors are (i) policy changes in contractor states, (ii) ECS-mining area boundary conflicts, (iii) environmental provisions in exploitation regulations at the international seabed (ER), (iv) ER implementation delays, and (v) mineral resource uncertainty. These findings provide actionable insights for contractors, policymakers, and stakeholders to optimize decision making in deep-sea mining projects.

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Record high CH4/N2 adsorption separation selectivity in a scalable metal-organic framework - Yan-Long Zhao; Xuefeng Bai; Xin Zhang; Zhang-Ye Han; Jian-Rong Li (Science Bulletin, 2025)

Co-doping graphitic carbon nitride with Fe atoms and oxygen-containing functional groups for the efficient photo-Fenton degradation of sulfamethoxazole - Ruiyan Zhang; Cong Yan; Qinghua Yan; Congzhe Ren; Wen Zhang; Xiaozhe Song; Xuyang Li; Lei Chen; Fangyuan Zhou; Rong Xue; Feng Shi; Chongqing Xu (Journal of Water Process Engineering, 2025)

Occurrence and distribution of PAHs in the Yangtze River and urban river waters of Nanjing, China: Insights from in situ DGT measurements - Qiuyu Rong; Hao Zhang; Yanying Li; Liying Yan; Jun Luo; Kevin C. Jones (Environmental Pollution, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Assessment of Geostationary Satellite Cloud Effective Radius over East China with In Situ Aircraft Measurements - Qiuli Zhang; Chao Liu; Rong Zhang; Jing Yang; Junxia Li; Bo Li; Feng Lu; Yan Yin; Hongchun Jin (Journal of Meteorological Research, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

A multi-task model for mill load parameter prediction using physical information and domain adaptation: Validation with laboratory ball mill - Yiwen Liu; Gaowei Yan; Shuyi Xiao; Fang Wang; Rong Li; Yusong Pang (Minerals Engineering, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Opposing island biogeographic effects of turnover and nestedness on beta-diversity of soil faunal communities between woodland and deforested grassland - Zengyan Li; Zengke Zhang; Anna Yang; Sufeng Pan; Junyong Zheng; Ling Mou; Wensheng Chen; Tian Zhang; Liyi Zhou; Wenhui You; David A. Wardle; En-Rong Yan (Applied Soil Ecology, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Green process for xylo-oligosaccharide production from acetic acid hydrolysis of sugarcane bagasse by an integrated membrane technology and activated carbon adsorption - Qian Li; Yan Li; Jianjian Niu; Xiaofeng Hang; Weifeng Cao; Rong Fan; Yinhua Wan (Journal of Environmental Management, 2025)

Rational screening of metal single-atom-doped ZSM-5 to promote ring-opening cracking of cycloalkanes to light olefins - Jiarong Lu; Qi Shen; Rong Fan; Guoliang Li; Yaqian Li; Xinyang Zhang; Hao Yan; Yibin Liu; Tao Liu; Xiaobo Chen (Fuel, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Scalable deposition of SnO2 ETL via SALD for large-area inverted perovskite solar modules - Xuewei Jiang; Bin Shan; Geng Ma; Yan Xu; Xing Yang; Wenbin Zhou; Chenhui Li; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Revisiting bipolar membrane electrodialysis for the production of monoprotic organic acids with different p K a and Mw - Rong Zhou; Zhiguo Dong; Xixi Ma; Lili Xue; Jinxin Liu; Jinfeng He; Weiwei Li; Li Sun; Chuanrun Li; Haiyang Yan (Chemical Engineering Journal, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

The key pathogenic factor GcSP2 of Geotrichum citri-aurantii plays an important role in disrupting citrus metabolism and immunity - Rong Liu; Haoxiang Zheng; Di Wang; Haijue Zhang; Yan Wu; Xue Li; Zhengfeng Liu; QingJun Kong; Xueyan Ren (Postharvest Biology and Technology, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Methoxyflavone glucosides and caffeoyl phenylethanoid glycoside from Lysionotus pauciflorus: their structures and anti-ferroptosis activity - Rena Takizawa; Tomoyo Minamizono; Daisuke Tsuji; Xiao-Jie Yan; Feng-Lai Lu; Xue-Rong Yang; Dian-Peng Li; Reiko Akagi; Yoshiki Kashiwada; Naonobu Tanaka (Journal of Natural Medicines, 2025)

Evaluation of metagenomic next-generation sequencing (mNGS) combined with quantitative PCR: cutting-edge methods for rapid diagnosis of non-invasive fungal rhinosinusitis - Xiao Liu; Shaoqin Zhou; Rong Yan; Caifeng Xia; Ruoning Xue; Zhe Wan; Ruoyu Li; Sybren de Hoog; Sarah A. Ahmed; Quangui Wang; Yinggai Song (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Effects of the types and ages of vegetation restoration on land surface roughness in the Eastern Hobq Desert, Northern China - Ji Feng; Yong-Sheng Wu; Li-Yuan Lu; Chasina Xi; Feng-Yan Wu; Chao-Yu Wang; Qiang Yin; Altantuya Dorjsuren; Rong-Liang Jia; Yu Qiao; Yuan-Fa Meng; Jie Yu (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Electrodialysis with ultrafiltration membrane for efficient isolation of oxymatrine from simulated eluent of traditional Chinese medicine - Zhiguo Dong; Rong Zhou; Zengqiang Wei; Yiwei Dong; Li Sun; Xixi Ma; Wenlong Liu; Qiuhua Li; Jinfeng He; Chuanrun Li; Haiyang Yan (Desalination, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

The change of environmental factors in the water near the Yangtze Estuary may induce the change of large yellow croaker fishery location there - Lina Cai; Jiahua Li; Xiaojun Yan; Rong Tang; Xinkai Zhang (Frontiers in Marine Science, 2024)
The large yellow croaker, an endemic migratory species in China’s coastal waters, holds considerable economic importance. It is very necessary and significant to study the spatio-temporal evolution of large yellow croaker fishery based on environmental factors. In this paper, the HY-1C/D Coastal Zone Imager was applied to reveal distributional details of suspended sediment concentration and chlorophyll-a concentration in large yellow croaker fishery. Furthermore, combined with multi-source data, the characteristics of other environmental parameters such as temperature, salinity, current, wind and fronts were analyzed to reveal the changing of large yellow croaker fishery location. The results show that: (1) The environmental factors of large yellow croaker fishery exhibit pronounced spatial and temporal characteristics. Generally, the temperature (9-28°C), salinity (20-34 ‰) and other water environmental factors of the fishing ground are conducive to the survival and growth of large yellow croaker. The formation and change of fishery are closely related to environmental factors in the water. (2) The change of environmental factors in the water may induce the change of large yellow croaker fishery location. Winter sea surface temperature has significantly risen over the past two decades (2004-2023). With the sea surface temperature rising by approximately 2°C west of 125°E, the overwintering ground has expanded westward, increasing by nearly 29%. In addition, the scale and number of offshore windmills increased by 836% and 456% respectively over the decade (2013-2023). In 2023, offshore wind farms cover an area of 145.47 km 2 and have 200 windmills. Wind turbine piles resembling artificial reefs. It can not only promote the waters vertical exchange to enhance the nutrients in upper waters but also provide a protective base for fish spawning. Thus, effectively attracting fish species. The construction of offshore wind farms has extended spawning ground north-westward to the mouth of the Yangtze River Estuary, expanding by nearly 21%. This study improved the cognition level of resources, habitat environment and change trend of large yellow croaker. It also provided technical support for the construction and protection of the large yellow croaker fishery.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

A joint-threshold Filippov model describing the effect of intermittent androgen-deprivation therapy in controlling prostate cancer - Aili Wang; Rong Yan; Haixia Li; Xiaodan Sun; Weike Zhou; Stacey R. Smith (Mathematical Biosciences, 2024)

Microplastics from polyvinyl chloride agricultural plastic films do not change nitrogenous gas emission but enhance denitrification potential - Xiaofang Ma; Zhijun Wei; Xiaomin Wang; Chenglin Li; Xueying Feng; Jun Shan; Xiaoyuan Yan; Rong Ji (Journal of Hazardous Materials, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Accumulation and depuration of 4,5-dihydro-KmTx2 from Karlodinium veneficum in the bivalves, Mercenaria mercenaria and Sinonovacula constricta - Yanrong Li; Rong Chen; Zhujun Zhu; Tong Mu; Zhaoshou Ran; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2024)

Genomic analysis of hypoxia-tolerant population of the Chinese mitten crab (Eriocheir sinensis) - Feng-yuan Yan; Yuan-feng Xu; Wen-rong Feng; Qing-hong He; Guo-an Hua; Wen-jing Li; Pao Xu; Jun Zhou; Yong-kai Tang (Fish & Shellfish Immunology, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

N, S-carbon quantum dots as inhibitor in pickling process of heat exchangers for enhanced performance in multi-stage flash seawater desalination - Bochuan Tan; Yan Liu; Haiqin Ren; Zhili Gong; Xin Li; Wenpo Li; Lei Guo; Rong Chen; Juxiang Wei; Qingwei Dai; Abeer A. AlObaid (Desalination, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Sulphur in apatite: a potential monitor of the magmatic redox state in the world-class gold fields of the North China Craton - Jia-Wei Liu; Lin Li; Sheng-Rong Li; M. Santosh; Mao-Wen Yuan; Masroor Alam; Shun-Feng Yan (International Geology Review, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Altered Function and Structure of the Cerebellum Associated with Gut–Brain Regulation in Crohn’s Disease: a Structural and Functional MRI Study - Yunfei Li; Yanling Zheng; Lan Rong; Yan Zhou; Zhen Zhu; Qian Xie; Zonghui Liang; Xiaohu Zhao (The Cerebellum, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

An origami microfluidic paper device based on core-shell Cu@Cu2S@N-doped carbon hollow nanocubes - Yuanyuan Li; Huinan Chen; Rong Huang; Dongmei Deng; Xiaoxia Yan; Liqiang Luo (Analytica Chimica Acta, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Inactivation of Aeromonas hydrophila in water by dielectric barrier discharge plasma: Efficiency, mechanism, and application safety - Le Wang; Zhenfei Zhu; Pengcheng Yan; Rong Zhang; Min Zhang; Xiangyu Wang; Guangzhou Qu; Tiecheng Wang; Ronghua Li (Journal of Water Process Engineering, 2024)

Small water body significantly contributes to nitrous oxide emissions in China's aquaculture - Xing Yan; Haojie Han; Xiaohan Li; Xiangmin Rong; Longlong Xia; Xiaoyuan Yan; Yongqiu Xia (Journal of Environmental Management, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Drought reduces peanut yield indirectly through regulating soil nematode community in a manipulative field experiment in central China - Cancan Zhao; Rong Fan; Xiaolin Li; Like Fan; Liwei Zhang; Xinyu Yan; Xiang Zhao; Yuan Miao; Yanfeng Sun; Yuanhu Shao; Guoyong Li; Shenglei Fu (Applied Soil Ecology, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Analysis of mild and severe neonatal enterovirus infections in a Chinese neonatal tertiary center: a retrospective case-control study - Junshuai Li; Jingjing Xie; Min Zhang; Zhuojun Xiao; Fan Zhang; Weiqing Huang; Yong Zhou; Weiqun Yan; Rong Zhang; Xiaoming Peng (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Development of a novel DGT passive sampler for measuring polycyclic aromatic hydrocarbons in aquatic systems - Qiuyu Rong; Yanying Li; Jun Luo; Liying Yan; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

Analysis of the transmission chain of carbapenem-resistant Enterobacter cloacae complex infections in clinical, intestinal and healthcare settings in Zhejiang province, China (2022–2023) - Zelin Yan; Xiaoyang Ju; Yanyan Zhang; Yuchen Wu; Yi Sun; Panfeng Xiong; Yan Li; Ruichao Li; Rong Zhang (Science of The Total Environment, 2024)

A specific module of ESCRT regulates STING activity termination by controlling STING degradation - Yuan Zhao; Chenxuan Zhou; Wenmin Tian; Yang Chen; Chongchong Zhao; Yan Li; Shixuan Wang; Yueguang Rong (Science Bulletin, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Multi-source unsupervised domain adaptive mill load forecasting method based on deep learning and fusion features - Yiwen Liu; Gaowei Yan; Rong Li; Shuyi Xiao; Mifeng Ren; Lan Cheng (Minerals Engineering, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Cultivation mode of Saccharina japonica impacts planktonic and epiphytic microbiomes - Yongwei Yan; Shanshan Wang; Shaojun Pang; Kuimei Liu; Lirong Chang; Xiaojun Rong; Jie Li (Algal Research, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Characterization of multi-copy C3 genes and association analysis of C3.1 polymorphism with GCRV resistance traits in Ctenopharyngodon idella - Jia-yang Huang; Zhao Lv; Bin Li; Yan-rong Ying; Le Yang; Tiao-yi Xiao; Shu-ting Xiong (Aquaculture, 2024)

Development and validation of an in situ high-resolution technique for measuring antibiotics in sediments - Yanying Li; Qiuyu Rong; Chao Han; Hanbing Li; Jun Luo; Liying Yan; Degao Wang; Kevin C. Jones; Hao Zhang (Journal of Hazardous Materials, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

A multi-species pest recognition and counting method based on a density map in the greenhouse - Zhiqin Zhang; Jiacheng Rong; Zhongxian Qi; Yan Yang; Xiajun Zheng; Jin Gao; Wei Li; Ting Yuan (Computers and Electronics in Agriculture, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Bi-directional prediction of hydrothermal carbonization characteristics of agroforestry and livestock wastes with variable components: Graph learning model-aided waste recycle - Zi-Kai Lin; Chao-Sheng Li; Rong-Rong Cai; Yan-Qiu Long (Journal of Cleaner Production, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Dissolved organic carbon and dissolved oxygen determine the nitrogen removal rate constant in small water bodies of intensive agricultural region - Xing Yan; Haojie Han; Xiaohan Li; Jiong Wen; Xiangmin Rong; Yongqiu Xia; Xiaoyuan Yan (Agriculture, Ecosystems & Environment, 2024)

Gut microbiome as a key monitoring indicator for reintroductions of captive animals - Guangping Huang; Dunwu Qi; Zhisong Yang; Rong Hou; Wenyu Shi; Fangqing Zhao; Zitian Li; Li Yan; Fuwen Wei (Conservation Biology, 2024)
Reintroduction programs seek to restore degraded populations and reverse biodiversity loss. To examine the hypothesis that gut symbionts could be used as an indicator of reintroduction success, we performed intensive metagenomic monitoring over 10 years to characterize the ecological succession and adaptive evolution of the gut symbionts of captive giant pandas reintroduced to the wild. We collected 63 fecal samples from 3 reintroduced individuals and 22 from 9 wild individuals and used 96 publicly available samples from another 3 captive individuals. By microbial composition analysis, we identified 3 community clusters of the gut microbiome (here termed enterotypes ) with interenterotype succession that was closely related to the reintroduction process. Each of the 3 enterotypes was identified based on significant variation in the levels of 1 of 3 genera: Clostridium , Pseudomonas , and Escherichia . The enterotype of captive pandas was Escherichia . This enterotype was gradually replaced by the Clostridium enterotype during the wild‐training process, which in turn was replaced by the Pseudomonas enterotype that resembled the enterotype of wild pandas, an indicator of conversion to wildness and a successful reintroduction. We also isolated 1 strain of Pseudomonas protegens from the wild enterotype, a previously reported free‐living microbe, and found that its within‐host evolution contributed to host dietary adaptation in the wild. Monitoring gut microbial structure provides a novel, noninvasive tool that can be used as an indicator of successful reintroduction of a captive individual to the wild.

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Application and evaluation of probiotics against red rot disease in Pyropia - Peiwen Weng; Huichao Yang; Zhaolan Mo; Wenbin Zhang; Yongwei Yan; Xiaojun Rong; Jie Li (Aquaculture, 2024)

Microplastics enhance nitrogen loss from a black paddy soil by shifting nitrate reduction from DNRA to denitrification and Anammox - Xiaofang Ma; Jun Shan; Yanchao Chai; Zhijun Wei; Chenglin Li; Ke Jin; Han Zhou; Xiaoyuan Yan; Rong Ji (Science of The Total Environment, 2024)

Enhancing the removal of chlorinated hydrocarbons from groundwater using a new BL5 microorganism with functional CS@ZVI materials - Zhiguo Chen; Wenqing Cao; Yan Li; Jingpeng Song; Yiyun Liu; Juncheng Liu; Rong Zhang; Rongxin Su; He Bai (Journal of Water Process Engineering, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

TBK1 upregulates the interferon response against virus by the TBK1-IRF3/7 axis in yellow catfish (Pelteobagrus fulvidraco) - Li-ming Xiong; Lei Zhang; Zhe Long; Xiang Zhao; Yan-rong Ying; Tiao-yi Xiao; Shu-ting Xiong (Fish & Shellfish Immunology, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

A Multi-Task Learning Based Runoff Forecasting Model for Multi-Scale Chaotic Hydrological Time Series - Hui Zuo; Gaowei Yan; Ruochen Lu; Rong Li; Shuyi Xiao; Yusong Pang (Water Resources Management, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Driving model of land use change on the evolution of carbon stock: a case study of Chongqing, China - Luoshan Zheng; Yangbing Li; Yan Chen; Rong Wang; Shijie Yan; Chunhua Xia; Bing Zhang; Jing’an Shao (Environmental Science and Pollution Research, 2023)

Phenolic and bisamide derivatives from Aglaia odorata and their biological activities - Xiaomeng Yang; Yan Yu; Panfeng Wu; Juan Liu; Yanan Li; Linlan Tao; Rong Tan; Xiaojiang Hao; Chunmao Yuan; Ping Yi (Natural Product Research, 2023)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

A novel active packaging film containing citronella oil: Preparation, characterization, antimicrobial activity and application in grape preservation - Weijie Zhao; Changcheng Li; Weijia Ma; Ruiwen He; Yan Rong; Shovra Sarker; Qi Liu; Fang Tian (Food Packaging and Shelf Life, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Changes in soil organic carbon stocks of forestlands and grasslands on the Loess Plateau, 1980–2015 - Gang Li; Shaobo Sun; Nan Lu; Rong Huang; Jianwu Yan; Fan Song; Jichang Han; Ying Wang (Journal of Cleaner Production, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Blockade of the Dopamine D3 Receptor Attenuates Opioids-Induced Addictive Behaviours Associated with Inhibiting the Mesolimbic Dopamine System - Rong-Rong Hu; Meng-Die Yang; Xiao-Yan Ding; Ning Wu; Jin Li; Rui Song (Neuroscience Bulletin, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

N, N-bis (2-hydroxyethyl) malonamide based amidoxime functionalized polymer immobilized in biomembranes for highly selective adsorption of uranium(VI) - Yang Li; Ze-Yang Wang; Qi Ren; Feng Zhang; Xu-Xin Li; Qiang Wu; Rong Hua; Ze-Yi Yan; Yun Wang (Chemosphere, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Impact of bentonite on greenhouse gas emissions during pig manure composting and its subsequent application - Jia-Ping Wu; Meng-Ling Li; Yan Wang; Shan Lin; Rong-Gui Hu; Rong-Biao Xiang (Journal of Environmental Management, 2023)

Widely targeted metabolomics and HPLC analysis elaborated the quality formation of Yunnan pickled tea during the whole process at an industrial scale - Yan Hou; Honglin Mao; Fengmei Lu; Cunqiang Ma; Shaoxian Zhu; Guoyou Li; Siqi Huang; Yi Zhang; Caiyou Lv; Rong Xiao (Food Chemistry, 2023)

Balanced phosphorus fertilization enhances soil bacterial network complexity to maintain multifunctionality and plant production in dryland agricultural systems - Lei Liu; Rong Yan; Li Zhu; Yu Yang; Zhiyuan Gao; Wenjie Yang; Jinshan Liu (Agriculture, Ecosystems & Environment, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

Hypervirulent Klebsiella pneumoniae detection methods: a minireview - Qi-bin Zhang; Peng Zhu; Shun Zhang; Yan-jing Rong; Zuo-an Huang; Li-wan Sun; Ting Cai (Archives of Microbiology, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Treatment of fresh leachate by anaerobic membrane bioreactor: On-site investigation, long-term performance and response of microbial community - Weifu Yan; Yulin Wang; Yemei Li; Chao Rong; Dou Wang; Chunxiao Wang; Yubo Wang; Yee-lok Yuen; Fanny Fong Wong; Ho-Kwong Chui; Yu-You Li; Tong Zhang (Bioresource Technology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Hyperglycemia symptom amelioration by Ascophyllum nodosum polysaccharides in mice with type 2 diabetes - Ligen Chen; Liang Shen; Lingyun Zhu; Fengwei Li; Xiaodong Ge; Xiujuan Xia; Hongwei Yan; Tingting Liu; Wei Xu; Rong Shao (Algal Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Emission of volatile organic compounds from landfill working surfaces: Formation potential of ozone and secondary organic aerosols - Silan Zhao; Rong Li; Shengwei Wang; Yanqing Liu; Wenjing Lu; Yan Zhao (Science of The Total Environment, 2023)

Involvement of Abnormal p-α-syn Accumulation and TLR2-Mediated Inflammation of Schwann Cells in Enteric Autonomic Nerve Dysfunction of Parkinson’s Disease: an Animal Model Study - Wenwen Jiang; Yue Cheng; Ye Wang; Jing Wu; Zhe Rong; Li Sun; Yan Zhou; Kezhong Zhang (Molecular Neurobiology, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

A cascade electro-dehydration process for simultaneous extraction and enrichment of uranium from simulated seawater - Ruirui Li; Huangying Wang; Junying Yan; Rong Fu; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Water Research, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

A direct electrochemical substitution electrodialytic system for CO2 conversion into high value-added soda - Huangying Wang; Haiyang Yan; Kang Peng; Junying Yan; Rong Fu; Ruirui Li; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Chemical Engineering Journal, 2023)

Ultra-stable, sensitive and broadband photodetector based on large-area 2D bismuth oxyselenide film for multiband image sensing - Shuai Ren; Shiyong Gao; Ping Rong; Lin Li; Mingyi Zhang; Huiqing Lu; Jun Yan; Duoduo Ling; Shujie Jiao; Jinzhong Wang (Chemical Engineering Journal, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

BPA exposure enhances the metastatic aggression of ovarian cancer through the ERα/AKT/mTOR/HIF-1α signaling axis - Xin Xie; Yan Zhu; Huimin Cheng; Haili Li; Yadi Zhang; Rong Wang; Wenyong Li; Fengrui Wu (Food and Chemical Toxicology, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

An endogenous neuropeptide hormone assists cancer cells in escaping from immune surveillance - Chang-Yu Yan; Yan-Ping Wu; Yi-Fang Li; Rong-Rong He (Science China Life Sciences, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Molecular detection and characterization of three novel parvoviruses belonging to two different subfamilies in zoo birds - Yan Wang; Yijie Sun; Xin Li; Rong Chen; Wang Li; Li Ji; Qifan Zhao; Likai Ji; Shixing Yang; Wen Zhang (Archives of Virology, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Abundant bacterial subcommunity is structured by a stochastic process in an agricultural system with P fertilizer inputs - Lei Liu; Li Zhu; Rong Yan; Yu Yang; Jonathan M. Adams; Jinshan Liu (Science of The Total Environment, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Ion transmembrane behaviors in selective electrodialysis for acid recovery: Impact of ion categories - Junying Yan; Huangying Wang; Haiyang Yan; Ruirui Li; Rong Fu; Weicheng Fu; Liang Ge; Baoying Wang; Yaoming Wang; Tongwen Xu (Desalination, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

CRISPR/Cas9-based point-of-care lateral flow biosensor with improved performance for rapid and robust detection of Mycoplasma pneumonia - Rong Zhu; Han Jiang; Chaoyou Li; Yan Li; Min Peng; Junfeng Wang; Qian Wu; Chao Yan; Qingli Bo; Jie Wang; Chenlin Shen; Panzhu Qin (Analytica Chimica Acta, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

The inhibition mechanism and death mode of Microcystis aeruginosa induced by the continuous pressure of artemisinin sustained-release microspheres (ASMs) - Cunhao Du; Lixiao Ni; Jakpa Wizi; Wenlu Sang; Shiyi Rong; Xianglan Li; Chu Xu; Yan Li; Xuqing Chen; Shiyin Li (Algal Research, 2023)

Nogo-A Mediated Endoplasmic Reticulum Stress During Myocardial Ischemic-Reperfusion Injury in Diabetic Rats - Yonghong Xiong; Yan Leng; Wei Li; Wenyuan Li; Hao Tian; Jie Tao; Rong Chen; Zhongyuan Xia (Cardiovascular Toxicology, 2023)

First report of fruit rot caused by Paramyrothecium foliicola on muskmelon in China - Jian Fei Huo; Yong Xia Ren; Yu Rong Yao; Hai Yan Ben; Xiu Yun Wen; Wen Lai Ren; Li Juan Yang; Wan Li Wang; Yong Juan Hao (Journal of Plant Pathology, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

The phosphorus harvest from low-temperature mainstream wastewater through iron phosphate crystallization in a pilot-scale partial nitritation/anammox reactor - Yan Guo; Eli Hendrik Sanjaya; Tianjie Wang; Chao Rong; Zibin Luo; Yi Xue; Hong Chen; Yu-You Li (Science of The Total Environment, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Biological magnetic ion exchange resin on advanced treatment of synthetic wastewater - Shanshan Xu; Yunbao Yan; Chendong Shuang; Qing Zhou; Rong Ji; Aimin Li (Bioresource Technology, 2023)

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Fertility assessment and nutrient conversion of hydrochars derived from co-hydrothermal carbonization between livestock manure and corn cob - Chao-sheng Li; Rong-rong Cai; Abdulla Hasan; Xiao-luan Lu; Xiao-xiao Yang; Yan-guo Zhang (Journal of Environmental Chemical Engineering, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Remodeled CD146+CD271+ Bone Marrow Mesenchymal Stem Cells from Patients with Polycythemia Vera Exhibit Altered Hematopoietic Supportive Activity - Chao Chen; Mingying Zhang; Rong Li; Jiajia Yuan; Jinqiang Yan; Yuhui Zhang; Wen Xing; Jie Bai; Yuan Zhou (Stem Cell Reviews and Reports, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Divergence of epibacterial community assemblage correlates with malformation disease severity in Saccharina japonica seedlings - Yongwei Yan; Shanshan Wang; Kuimei Liu; Zhaolan Mo; Huichao Yang; Xiaojun Rong; Jie Li (Frontiers in Marine Science, 2023)
Malformation disease (MD) is one of the major constraints in the mariculture of the commercially important seaweed Saccharina japonica , which can cause severe losses of the kelp seedlings in the production process. However, the pathogenesis of MD remains largely undetermined. In this study, using cultivation experiments under laboratory conditions, MD severity was estimated for the young sporophytes of S. japonica , which were separately cultivated under different treatment conditions, including light intensity, duration of light exposure, and maturity level of the parent kelp. The associations between MD severity and epibacterial community divergence and assembly patterns were characterized. Higher MD severity significantly correlated with longer light exposure, and with both unmatured and overmatured parent kelp. The bacterial classes γ-Proteobacteria and α-Proteobacteria dominated all samples, but different MD severities were associated with different epibacterial communities. Comparisons of predicted functions for epibacterial communities revealed that longer light exposure led to a depletion in development and regeneration, while overmatured parent kelp resulted in a depletion in glycan biosynthesis and metabolism. Functional comparisons of the epibacterial communities between normal and unmatured parent kelp-generated seedlings revealed significantly different categories related to metabolism, environmental information processing, cellular processes, drug resistance, and bacterial infection. The significantly different pathways between groups, notably those related to bacterial infection and cellular processes, were partly consistent with the differences in bacterial compositions. The assembly of epiphytic bacterial communities was predominately governed by deterministic processes, and less impact was determined when there was significantly higher MD severity except when using overmatured parent kelp. Co-occurrence networks of the epibacterial communities associated with higher MD severity contained fewer nodes and exhibited lower modularity, but had higher graph density and degrees compared with those of seedlings with lower MD severity, indicating more complicated interactions. Nesterenkonia , Glycocaulis , Halomonas , Pseudoalteromonas , Pseudomonas , Loktanella , and Cobetia were frequently determined keystone taxa in communities associated with higher MD severity. The present study enhances our understanding of the factors significantly associated with MD severity and the potential roles of epimicrobiome in determining the disease severity, which will be useful for disease management in the future.

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

A new method for wear estimation of TBM disc cutter based on energy analysis - Lei She; She-rong Zhang; Chao Wang; Yan-long Li; Min Du (Tunnelling and Underground Space Technology, 2023)

Mechanical and microscopic properties of soil according to the rate of increase in pore water pressure - Zhao Duan; Zhen-Yan Li; Yan-Bin Wu; Bing Niu; Rong-Jian Shen (Soil and Tillage Research, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Degradation of antibiotics by electrochemical advanced oxidation processes (EAOPs): Performance, mechanisms, and perspectives - Qingbin Yuan; Siyao Qu; Rong Li; Zheng-Yang Huo; Yan Gao; Yi Luo (Science of The Total Environment, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

Health risk assessment of volatile organic compounds (VOCs) emitted from landfill working surface via dispersion simulation enhanced by probability analysis - Rong Li; Jiayi Yuan; Xiang Li; Silan Zhao; Wenjing Lu; Hongtao Wang; Yan Zhao (Environmental Pollution, 2023)

Micro-mesoporous graphitized carbon fiber as hydrophobic adsorbent that removes volatile organic compounds from air - Min Yan; Yang Rong; Feng Wu; Zhixiong You; Dashan Wang; Xudong Yang; Zhengping Hao; Jinjun Li; Zhongshen Zhang (Chemical Engineering Journal, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Quality improvement of the thermal gel of horse mackerel by sodium citrate and its inhibition of the insoluble metalloproteinase - Yan-Rong Jiang; Asami Yoshida; Megumi Ohta; Yi-Li Gao; Erika Noguchi; Koichi Kuwahara; Kenji Hara; Kiyoshi Osatomi (Fisheries Science, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

The coupling effect of socio-economic and eco-environment and land use transformation in mountainous areas—a case of the Fengjie County in the Three Gorges Reservoir Area, China - Chunhua Xia; Yangbing Li; Jingan Shao; Shijie Yan; Yan Chen; Luoshan Zheng; Rong Wang (Environmental Science and Pollution Research, 2022)

The Improving of Cd2+ Adsorption Performance of Hydrochar Obtained from Corn Straw Waste with KOH Activation - Yan Shi; Heng Li; Yushi Rong; Li Bai; Mingshu Chi; Xiuling Xu; Chenglin Li; Hao Bai; Yue Liu (Water, Air, & Soil Pollution, 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Occurrence and damage of epidemic fungal diseases in middle and late stages of sugarcane growth in Yunnan Province of China - Wen-Feng Li; Xiao-Yan Wang; Hong-Li Shan; Rong-Yue Zhang; Yin-Hu Li; Wen-Jie Lu; Ying-Kun Huang (European Journal of Plant Pathology, 2022)

Tetramethylpyrazine protects neural stem cells against sevoflurane-induced toxicity through Akt/GSK-3β pathway - Yan Feng; Kui Wang; Ning Wang; Pengyu Jia; Lei Zhang; Haozheng Yuan; Pan Lu; Yang Lu; Hong Zhang; Rong Li; Yan Zhang; Qianqian Li; et al. (Metabolic Brain Disease, 2022)

Assessing the Impact of Atrazine on the Availability of Arsenic in Soils Using DGT Technique - Yanying Li; Liying Yan; Qiuyu Rong; Jun Luo; Hao Zhang; Kevin C. Jones (Bulletin of Environmental Contamination and Toxicology, 2022)

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Development of Physiology Based Pharmacokinetic Model to Predict the Drug Interactions of Voriconazole and Venetoclax - Ji Dong; Shuai-bing Liu; Jony Md Rasheduzzaman; Chen-rong Huang; Li-yan Miao (Pharmaceutical Research, 2022)

Dynamic p-y curves for vertical and batter pile groups in liquefied sand - Jian Zhang; Yurun Li; Xian Rong; Yan Liang (Earthquake Engineering and Engineering Vibration, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Comment on “Relationship of Circulating Copper Level with Gestational Diabetes Mellitus: a Meta-analysis and Systemic Review” - Shu-ping Li; Xiao-ping Zhang; Xin-hong Cui; Li-juan Zhao; Yan-jun Rong (Biological Trace Element Research, 2022)

HucMSC-Ex alleviates inflammatory bowel disease via the lnc78583-mediated miR3202/HOXB13 pathway - Yuting Xu; Li Zhang; Dickson Kofi Wiredu Ocansey; Bo Wang; Yilin Hou; Rong Mei; Yongmin Yan; Xu Zhang; Zhaoyang Zhang; Fei Mao (Journal of Zhejiang University-SCIENCE B, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Effect of Fertilization Regimes and Seasonal Change on nosZ-Denitrifying Bacterial Community in a Double-Rice Paddy Field - Jiangwen Nie; Yong Zhou; Wei Yang; Shaoqiu Li; Haoxuan Li; Jianwei Wu; Chengwei Li; Xiaoyuan Yan; Rong Zhu; Bo Zhu; Zhangyong Liu (Journal of Soil Science and Plant Nutrition, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Does the institutional environment influence corporate social responsibility? Consideration of green investment of enterprises—evidence from China - Shu-Rong Han; Pei Li; Jian-Jun Xiang; Xiang-Hua Luo; Chun-Yan Chen (Environmental Science and Pollution Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Serum- and Feeder-Free Culture of Juvenile Monkey Female Germline Stem Cells and Testosterone Regulation of their Self-Renewal - Xiaoyong Li; Xiaoying Yao; Chunlan Mu; Zhaoxia Wang; Rong Hu; Yan Chang; Ji Wu (Stem Cell Reviews and Reports, 2022)

Genetic diversity of Lathyrus sp collected from different geographical regions - Md. Mosiur Rahman; Md. Ruhul Quddus; Md. Omar Ali; Rong Liu; Mengwei Li; Xin Yan; Guan Li; Yishan Ji; Md. Monoar Hossain; Chenyu Wang; Ashutosh Sarker; Tao Yang; et al. (Molecular Biology Reports, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

The addition of sawdust reduced the emission of nitrous oxide in pig manure composting by altering the bacterial community structure and functions - Chao Liu; Jiao Yan; Qian Huang; Hongjun Liu; Cece Qiao; Rong Li; Biao Shen; Qirong Shen (Environmental Science and Pollution Research, 2022)

Experimental study of vertical and batter pile groups in saturated sand using a centrifuge shaking table - Zhang Jian; Li Yurun; Yan Zhixiao; Huang Da; Rong Xian; Liang Yan (Earthquake Engineering and Engineering Vibration, 2022)

miR-21 Exerts Anti-proliferative and Pro-apoptotic Effects in LPS-induced WI-38 Cells via Directly Targeting TIMP3 - Jin-Xiu Li; You Li; Tian Xia; Feng-Yan Rong (Cell Biochemistry and Biophysics, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

Molecular cloning of myosin chaperone uncoordinate-45B (UNC-45B) and its heat stress response in the muscle of Pacific bluefin tuna Thunnus orientalis - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Uno Yamashita; Yan-Rong Jiang; Xiao-Mi Sun; Kazuya Shirota; Yasuhiko Shiina; Kiyoshi Osatomi (Fisheries Science, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Hippocampal Interneurons are Required for Trace Eyeblink Conditioning in Mice - Wei-Wei Zhang; Rong-Rong Li; Jie Zhang; Jie Yan; Qian-Hui Zhang; Zhi-An Hu; Bo Hu; Zhong-Xiang Yao; Hao Chen (Neuroscience Bulletin, 2021)
While the hippocampus has been implicated in supporting the association among time-separated events, the underlying cellular mechanisms have not been fully clarified. Here, we combined in vivo multi-channel recording and optogenetics to investigate the activity of hippocampal interneurons in freely-moving mice performing a trace eyeblink conditioning (tEBC) task. We found that the hippocampal interneurons exhibited conditioned stimulus (CS)-evoked sustained activity, which predicted the performance of conditioned eyeblink responses (CRs) in the early acquisition of the tEBC. Consistent with this, greater proportions of hippocampal pyramidal cells showed CS-evoked decreased activity in the early acquisition of the tEBC. Moreover, optogenetic suppression of the sustained activity in hippocampal interneurons severely impaired acquisition of the tEBC. In contrast, suppression of the sustained activity of hippocampal interneurons had no effect on the performance of well-learned CRs. Our findings highlight the role of hippocampal interneurons in the tEBC, and point to a potential cellular mechanism subserving associative learning.

Evaluation of field resistance to brown stripe disease in novel and major cultivated sugarcane varieties in China - Xiao-Yan Wang; Xiao-Yan Cang; Wei Qin; Hong-Li Shan; Rong-Yue Zhang; Chang-Mi Wang; Wen-Feng Li; Ying-Kun Huang (Journal of Plant Pathology, 2021)

Colonization Characteristics of Poplar Fungal Disease Biocontrol Bacteria N6-34 and the Inhibitory Effect on Pathogenic Fungi by Real-Time Fluorescence Quantitative PCR Detection - Rong-bo Sa; Jun-li Zhang; Ji-zheng Sun; Yan-xia Gao (Current Microbiology, 2021)

Farnesoic acid methyltransferase 6 (BmFAMeT6) interrelates with moltinism of dominant trimolter in silkworm, Bombyx mori - Liang Zhang; Xiuzhi Li; Tian Li; Rong Xiong; Yan Li; Dongsheng Yan; Ping Chen (Biologia, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Clinical study on empirical and diagnostic-driven (pre-emptive) therapy of voriconazole in severe aplastic anaemia patients with invasive fungal disease after intensive immunosuppressive therapy - Yuhong Wu; Li Yan; Huaquan Wang; Hong Liu; Limin Xing; Rong Fu; Zonghong Shao (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Effect of bFGF on fibroblasts derived from the golden snub-nosed monkey - Xin Liu; Hao Wei; Jing Yang; Jingjing Li; Pei Zhang; Yuli Li; Rong Hou; Jinlian Hua; Xingrong Yan; Baoguo Li (Primates, 2021)

Noroleanane-type triterpenoids from Dolichos trilobus L. and their anti-α-glucosidase activities - Ming Luo; Yan-Hong Li; Ya Lu; Yan Yuan; Rong-Sheng Ruan; Yong-Ming Chuan; Kai Tian; Xiang-Zhong Huang (Natural Product Research, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

Application of a Two-Analyte Integrated Population Pharmacokinetic Model to Evaluate the Impact of Intrinsic and Extrinsic Factors on the Pharmacokinetics of Polatuzumab Vedotin in Patients with Non-Hodgkin Lymphoma - Dan Lu; Tong Lu; Rong Shi; Leonid Gibiansky; Priya Agarwal; Colby S. Shemesh; Randall C. Dere; Uzor Ogbu; Jamie Hirata; Pascal Chanu; Sandhya Girish; Jin Yan Jin; et al. (Pharmaceutical Research, 2020)
Purpose The established two-analyte integrated population pharmacokinetic model was applied to assess the impact of intrinsic/extrinsic factors on the pharmacokinetics (PK) of polatuzumab vedotin (pola) in patients with non-Hodgkin lymphoma (NHL) following bodyweight-based dosing. Methods Model simulations based on individual empirical Bayes estimates were used to evaluate the impact of intrinsic/extrinsic factors as patient subgroups on Cycle 6 exposures. Intrinsic factors included bodyweight, age, sex, hepatic and renal functions. Extrinsic factors included rituximab/obinutuzumab or bendamustine combination with pola and manufacturing process. The predicted impact on exposures along with the established exposure-response relationships were used to assess clinical relevance. Results No clinically meaningful differences in Cycle 6 pola exposures were found for the following subgroups: bodyweight 100–146 kg versus 38–<100 kg, age ≥ 65 years versus <65 years, female versus male, mild hepatic impairment versus normal, mild-to-moderate renal impairment versus normal. Co-administration of rituximab/obinutuzumab or bendamustine, and change in the pola manufacturing process, also had no meaningful impact on PK. Conclusions In patients with NHL, bodyweight-based dosing is adequate, and no further dose adjustment is recommended for the heavier subgroup (100–146 kg). In addition, no dose adjustments are recommended for other subgroups based on intrinsic/extrinsic factors evaluated.

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Retraction Note to: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-qian Guo; Yu Chen; Bai-bing Mi; Shao-nong Dang; Dou-dou Zhao; Rong Liu; Hong-li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2020)

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

Molecular evolution of GII.P17-GII.17 norovirus associated with sporadic acute gastroenteritis cases during 2013–2018 in Zhoushan Islands, China - Can Chen; Bing Wu; Hui Zhang; Ke-Feng Li; Rong Liu; Hong-Ling Wang; Jian-Bo Yan (Virus Genes, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Decrypting the crosstalk of noncoding RNAs in the progression of IPF - Yujuan Wang; Han Xiao; Fenglian Zhao; Han Li; Rong Gao; Bingdi Yan; Jin Ren; Junling Yang (Molecular Biology Reports, 2020)
Idiopathic pulmonary fibrosis (IPF) is an agnogenic, rare, and lethal disease, with high mortality and poor prognosis and a median survival time as short as 3 to 5 years after diagnosis. No effective therapeutic drugs are still not available not only in clinical practice, but also in preclinical phases. To better and deeper understand pulmonary fibrosis will provide more effective strategies for therapy. Mounting evidence suggests that noncoding RNAs (ncRNAs) and their interactions may contribute to lung fibrosis; however, the mechanisms underlying their roles are largely unknown. In this review, we systematically summarized the recent advances regarding the crucial roles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) and crosstalk among them in the development of IPF. The perspective for related genes was well highlighted. In summary, ncRNA and their interactions play a key regulatory part in the progression of IPF and are bound to provide us with new diagnostic and therapeutic targets.

Photoprotection capacity of microalgae improved by regulating the antenna size of light-harvesting complexes - Guang-Rong Hu; Yong Fan; Yan-Lin Zheng; Feng Xu; Lei Zhang; Fu-Li Li (Journal of Applied Phycology, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

The Monitoring of the Pollution Degree of Maize Under Copper Stress - Chao Zhang; Keming Yang; Kunpeng Rong; Feng Cheng; Yan Li (Journal of the Indian Society of Remote Sensing, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Spectral Characteristics and the Study of Pollution Degree of Maize Leaves Under Copper and Lead Stress - Chao Zhang; Keming Yang; Yan Li; Feng Cheng; Kunpeng Rong (Journal of the Indian Society of Remote Sensing, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Spontaneous mutations in FgSAD1 suppress the growth defect of the Fgprp4 mutant by affecting tri‐snRNP stability and its docking in Fusarium graminearum - Xiaoping Li; Zhili Fan; Ming Yan; Jia Qu; Jin‐Rong Xu; Qiaojun Jin (Environmental Microbiology, 2019)
Summary FgPrp4, the only kinase in the spliceosome, is not essential for viability, but is important for splicing efficiency in Fusarium graminearum . The Fgprp4 deletion mutant had severe growth defects but often produced spontaneous suppressors with faster growth rate. To better understand the suppression mechanism, we identified and characterized spontaneous mutations in the tri‐snRNP‐specific protein, FgSad1, which suppressed the growth defects of Fgprp4 . The L512P mutation was verified for its suppressive effects on Fgprp4 , suggesting that mutations in FgSad1 may have effects involving FgPrp4 phosphorylation on FgSad1. Phosphoproteomics analysis showed that FgSad1 may not be the direct substrate of FgPrp4 kinase. Furthermore, truncation analysis showed that the N‐terminal, extra RS‐rich region of FgSad1 is critical for its function and is post‐translationally modified. The P258S or S269P mutations in FgSad1 increased its interactions with the U5 protein FgPrp8 and the U4/U6 protein FgPrp31, which may result in tri‐snRNP stabilization. Additionally, the D76N mutation increased the association of FgSad1 with the U2 snRNP. These data indicate that suppressor mutations in FgSad1 increase the stability of the tri‐snRNP and/or the affinity of FgSad1 with U2 snRNP and therefore potentially facilitate the docking of tri‐snRNP into the spliceosome.

Effects of demethylating reagent 5-aza-2′-deoxycytidine on the growth and cephalotaxine production in Cephalotaxus mannii suspension cells - Li-Rong Wei; Wang-Yan Qin; Yong-Cheng Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Simulation of the Northern and Southern Hemisphere Annular Modes by CAMS-CSM - Sulan Nan; Junli Yang; Yan Bao; Jian Li; Xinyao Rong (Journal of Meteorological Research, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Molecular cloning and functional characterization of a seed-specific VvβVPE gene promoter from Vitis vinifera - Peijie Gong; Rong Wei; Yan Li; Ruipu Wang; Yujin Tang; Ling Wang; Huijun Zhu; Yuejin Wang; Chaohong Zhang (Planta, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

A new actinomycin Z analogue with an additional oxygen bridge between chromophore and β -depsipentapeptide from Streptomyces sp. KIB-H714 - Miao Dong; Pei Cao; Ya-Tuan Ma; Jianying Luo; Yijun Yan; Rong-Tao Li; Sheng-Xiong Huang (Natural Product Research, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Onosmanones A and B, two novel quinonoid xanthenes from Onosma paniculatum - Li-Qiu Quan; Wei-Feng Dai; Fei Li; Yan-Hong Li; Xuan-Qin Chen; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Soil pre-fumigation could effectively improve the disease suppressiveness of biofertilizer to banana Fusarium wilt disease by reshaping the soil microbiome - Zongzhuan Shen; Chao Xue; Paul W. J. Taylor; Yannan Ou; Beibei Wang; Yan Zhao; Yunze Ruan; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Fisheries in Chinese seas: What can we learn from controversial official fisheries statistics? - Bin Kang; Min Liu; Xiao-Xia Huang; Jun Li; Yun-Rong Yan; Chiao-Chuan Han; Shao-Bo Chen (Reviews in Fish Biology and Fisheries, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

The complete mitochondrial genome sequence of Anthracoceros coronatus (Bucerotiformes: Bucerotidae) - Rong Li; Yanyan Chen; Haiya Yan; Chunqing Li; Heng Xiao; Shanyuan Chen (Conservation Genetics Resources, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Effects of probiotic on microfloral structure of live feed used in larval breeding of turbot Scophthalmus maximus - Yan Jiang; Zheng Zhang; Yingeng Wang; Yayun Jing; Meijie Liao; Xiaojun Rong; Bin Li; Guiping Chen; Hesen Zhang (Journal of Oceanology and Limnology, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Kinematic Outcome Measures using Target-Reaching Arm Movement in Stroke - Qianqian Yang; Yuan Yang; Jie Luo; Le Li; Tiebin Yan; Rong Song (Annals of Biomedical Engineering, 2017)

Polyol monoterpenes isolated from Chenopodium ambrosioides - Shu-Qun Hou; Yan-Hong Li; Xiang-Zhong Huang; Rong Li; Huai Lu; Kai Tian; Rong-Sheng Ruan; Yu-Kui Li (Natural Product Research, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

An efficient and green reaction of isatins, 3-amino-1-phenyl-2-pyrazolin-5-one (3-amine-1H-pyrazole), and β-diketone in aqueous medium - Zhansheng Wang; Hui Xu; Lirong Yan; Qingyang Li; Liangce Rong (Molecular Diversity, 2017)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Changes in the Intestinal Microbiota of Gibel Carp (Carassius gibelio) Associated with Cyprinid herpesvirus 2 (CyHV-2) Infection - Rong She; Tong-Tong Li; Dan Luo; Jia-Bao Li; Liu-Yi Yin; Huan Li; Yao-Min Liu; Xiang-Zhen Li; Qi-gui Yan (Current Microbiology, 2017)

Two new Anti-TMV active chalconoid analogues from the root of Phyllanthus emblica - He Yan; Li Rong Han; Xing Zhang; Jun Tao Feng (Natural Product Research, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Diversity of Eukaryotic Algae in Propylene Oxide Saponification Wastewater Activated Sludge - Rong He; Xiangyu Fan; Pengfei Gu; Yan Ji; Junyu Shen; Ruirui Li; Yumei Li; Qiang Li (Water Conservation Science and Engineering, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Identification of a New Rice Low-Tiller Mutant and Association Analyses Based on the SLAF-seq Method - Yan Li; Xiao-Fang Zeng; Yi-Chen Zhao; Jian-Rong Li; De-Gang Zhao (Plant Molecular Biology Reporter, 2017)

The effect of light on the cellular stoichiometry of Chlorella sp. in different growth phases: implications of nutrient drawdown in batch experiments - Jing Liu; Zhe Li; Jing-song Guo; Yan Xiao; Fang Fang; Rong-cong Qin; Ling-ling Zhang (Journal of Applied Phycology, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

MiR-449a regulates autophagy to inhibit silica-induced pulmonary fibrosis through targeting Bcl2 - Ruhui Han; Xiaoming Ji; Rong Rong; Yan Li; Wenxi Yao; Jiali Yuan; Qiuyun Wu; Jingjin Yang; Weiwen Yan; Lei Han; Baoli Zhu; Chunhui Ni (Journal of Molecular Medicine, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

Palaeoproterozoic magmatic–metamorphic history of the Quanji Massif, Northwest China: implications for a single North China-Quanji-Tarim craton within the Columbia supercontinent? - Chao Wang; Rong-She Li; Meng Li; Joseph G. Meert; Yan Peng (International Geology Review, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

A Real-time monitoring and early warning system for landslides in Southwest China - Neng-pan Ju; Jian Huang; Run-qiu Huang; Chao-yang He; Yan-rong Li (Journal of Mountain Science, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Exogenous hydrogen peroxide enhanced the thermotolerance of Festuca arundinacea and Lolium perenne by increasing the antioxidative capacity - Yan Wang; Jie Zhang; Jian-Long Li; Xin-Rong Ma (Acta Physiologiae Plantarum, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Changes in the transcriptomic profiles of maize roots in response to iron-deficiency stress - Yan Li; Nian Wang; Fengtao Zhao; Xuejiao Song; Zhaohua Yin; Rong Huang; Chunqing Zhang (Plant Molecular Biology, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

Systemic Evaluation of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Ai-Hua Zhu; Yan-Rong Hu; Wei Liu; Feng Gao; Jian-Xin Li; Li-Hui Zhao; Gang Chen (Cell Biochemistry and Biophysics, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

A new modified sesquiterpene glycoside from Cupressus chengiana - Yan Lin; Rong-Jiao Li; Yan Li; Brian D. McGarvey; Hai-Feng Wu; Xiao-Ling Wang (Natural Product Research, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Arbuscular mycorrhizal fungi: potential biocontrol agents against the damaging root hemiparasite Pedicularis kansuensis? - Xiao-Lin Sui; Ai-Rong Li; Yan Chen; Kai-Yun Guan; Lu Zhuo; Yan-Yan Liu (Mycorrhiza, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Effect of lithology and structure on seismic response of steep slope in a shaking table test - Han-xiang Liu; Qiang Xu; Yan-rong Li (Journal of Mountain Science, 2014)

Diversity of bacterioplankton in coastal seawaters of Fildes Peninsula, King George Island, Antarctica - Yin-Xin Zeng; Yong Yu; Zong-Yun Qiao; Hai-Yan Jin; Hui-Rong Li (Archives of Microbiology, 2014)

Silencing Pax3 by shRNA inhibits the proliferation and differentiation of duck (Anas platyrhynchos) myoblasts - Rong-Ping Zhang; He-He Liu; Hao-Han Wang; Yan Wang; Chun-Chun Han; Liang Li; Hua He; Heng-Yong Xu; Feng Xu; Ji-Wen Wang (Molecular and Cellular Biochemistry, 2014)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Rhynchophylline-induced vasodilation in human mesenteric artery is mainly due to blockage of L-type calcium channels in vascular smooth muscle cells - Peng-Yun Li; Xiao-Rong Zeng; Jun Cheng; Jing Wen; Isao Inoue; Yan Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

Engineering geological assessment for route selection of railway line in geologically active area: A case study in China - Run-qiu Huang; Yan-rong Li; Ke Qu; Ke Wang (Journal of Mountain Science, 2013)
The Cheng-Lan railway links Chengdu, a central city in Southwestern China, and Lanzhou, a central city in Northwestern China. The railway passes through the Longmenshan fault zone (Wenchuan earthquake happened there on May 12, 2008), Minjiang fault zone, and Dongkunlun fault zone, which are all active. It runs over the Yangtze River and the Yellow River, and crosses high mountains and deep valleys. There exists, along the railway’s alignment, different kinds of strata of hard granite and soft, weak metamorphic rocks such as carbonaceous slate, schist, and phyllite. It is, therefore, a key issue for such an infrastructure construction to assess the engineering geological conditions and risks, so as to mitigate or avoid possible georisks and to offer optional designs. Geological survey and georisk assessment along the railway corridor are carried out. Special attention is given to active faults, earthquakes and seismic zones. Based on these, discussions about geological aspects for route selection of the railway are conducted and countermeasures for georisk control are proposed accordingly. Main conclusions are achieved as follows: (1) Geohazards such as landslides, rockfalls and debries flows dominate both the route selection of the railway and the engineering structures (e.g., tunnels or bridges) adopted; (2) Tunnel has been proved to be an excellent structure for linear engineering in geologically active area; and (3) In the case where avoiding is impractical, necessary protection measures should be taken to engineering slopes in high earthquake intensity areas, especially the area with earthquake of Ms. 8 or greater.

Reduction of N-Nitrosodimethylamine (NDMA) in Aqueous Solution by Nanoscale Fe/Al2(SO4)3 - Lin Lin; Bin Xu; Yi-Li Lin; Lie Yan; Kai-Yuan Shen; Sheng-Ji Xia; Chen-Yan Hu; Rong Rong (Water, Air, & Soil Pollution, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Lack of association between SLCO1B1 polymorphism and the lipid-lowering effects of atorvastatin and simvastatin in Chinese individuals - Qiang Fu; Yan-Peng Li; Yuan Gao; Song-Hua Yang; Pei-Qi Lu; Min Jia; Li-Rong Zhang (European Journal of Clinical Pharmacology, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Permeability and sedimentation characteristics of pleistocene fluvio-glacial deposits in the Dadu river valley, Southwest China - Guo-xiang Tu; Run-qiu Huang; Hui Deng; Yan-rong Li (Journal of Mountain Science, 2013)

SIRT1 inhibits TNF-α-induced apoptosis of vascular adventitial fibroblasts partly through the deacetylation of FoxO1 - Weirong Wang; Chunfang Yan; Jiye Zhang; Rong Lin; Qinqin Lin; Lina Yang; Feng Ren; Jianfeng Zhang; Meixi Ji; Yanxiang Li (Apoptosis, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Diversity of bacteria in surface ice of Austre Lovénbreen glacier, Svalbard - Yin-Xin Zeng; Ming Yan; Yong Yu; Hui-Rong Li; Jian-Feng He; Kun Sun; Fang Zhang (Archives of Microbiology, 2013)

Molecular and pathogenic characterization of new Xanthomonas oryzae pv. oryzae strains from the coastline region of Fangchenggang city in China - Shu-Qing Yang; Shu-Yan Liu; Shuai Zhao; Yan-Hua Yu; Rong-Bai Li; Cheng-Jie Duan; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Episodic orogeny deduced from coeval sedimentary sequences in the foreland basin and its implication for uplift process of Longmen Mountain, China - Yong Li; De-chen Su; Rong-jun Zhou; Hai-bing Li; Alexander L. Densmore; Liang Yan; Zhao-kun Yan (Journal of Mountain Science, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Clinical characteristics of hepatitis B virus infection in middle school students born after the universal infant vaccination program in Shanghai, China - Wei-Ling Wang; Zhi-Jun Shu; Li-Xia Zhou; Yan-Rong Zhao (Archives of Virology, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Protective effect of andrographolide against concanavalin A-induced liver injury - Guojun Shi; Zhijian Zhang; Rong Zhang; Xiaofang Zhang; Yan Lu; Jian Yang; Di Zhang; Zhiguo Zhang; Xiaoying Li; Guang Ning (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

PNAS-4 expression and its relationship to p53 in colorectal cancer - Bin Zhou; Hui Yan; Yuan Li; Rong Wang; Keling Chen; Zongguang Zhou; Xiaofeng Sun (Molecular Biology Reports, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

Effects of Schisandra sphenanthera extract on the blood concentration of tacrolimus in renal transplant recipients - Hua-Wen Xin; Qing Li; Xiao-Chun Wu; Yan He; Ai-Rong Yu; Lei Xiong; Ying Xiong (European Journal of Clinical Pharmacology, 2011)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Expressions of thermostable bacterial cellulases in tobacco plant - Xi-ran Jiang; Xiao-ya Zhou; Wen-yan Jiang; Xiao-rong Gao; Wen-li Li (Biotechnology Letters, 2011)

Molecular characterization and expression patterns of Lbx1 in porcine skeletal muscle - Zhe Chao; Jian Wu; Rong Zheng; Feng-E. Li; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Effects of elevated CO2 levels on root morphological traits and Cd uptakes of two Lolium species under Cd stress - Yan Jia; Shi-rong Tang; Xue-hai Ju; Li-na Shu; Shu-xing Tu; Ren-wei Feng; Lorenzino Giusti (Journal of Zhejiang University-SCIENCE B, 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

A Proteomic Investigation of B Lymphocytes in an Autistic Family: A Pilot Study of Exposure to Natural Rubber Latex (NRL) May Lead to Autism - Chen Shen; Xin-liang Zhao; Weina Ju; Xiao-bing Zou; Li-rong Huo; Wu Yan; Jun-hua Zou; Guo-di Yan; Edmund C. Jenkins; W. Ted Brown; Nanbert Zhong (Journal of Molecular Neuroscience, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Sequence Analysis of the Lactoferrin Gene and Variation of g.7605C→T in 10 Chinese Indigenous Goat Breeds - Jing-Fen Kang; Xiang-Long Li; Hui-Qin Zheng; Rong-Yan Zhou; Lan-Hui Li; Hong-Yuan Zhao (Biochemical Genetics, 2011)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Differential miRNA expression and their target genes between NGX6-positive and negative colon cancer cells - Xiao-Yan Wang; Ming-Hua Wu; Fen Liu; Yu Li; Nan Li; Gui-Yuan Li; Shou-Rong Shen (Molecular and Cellular Biochemistry, 2010)

Construction and characterization of a full-length infectious clone from a fast-replicating, X4-tropic HIV-1 subtype B′ isolate - Shou-li Wu; Yan-sheng Yan; Ping-ping Yan; Hai-long Huang; Hui-rong Wang (Archives of Virology, 2010)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Using DNA barcodes to identify a bird involved in a birdstrike at a Chinese airport - Rong Yang; Xiaobing Wu; Peng Yan; Xiaoqiang Li (Molecular Biology Reports, 2010)

Inhalable Microparticles as Carriers for Pulmonary Delivery of Thymopentin-Loaded Solid Lipid Nanoparticles - Yan-Zhen Li; Xun Sun; Tao Gong; Jie Liu; Jiao Zuo; Zhi-Rong Zhang (Pharmaceutical Research, 2010)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Expression and characterization of two domains of Pinellia ternata agglutinin (PTA), a plant agglutinin from Pinellia ternata with antifungal activity - Li-Jun Ling; Yan-Zhuo Yang; Yu-Rong Bi (World Journal of Microbiology and Biotechnology, 2010)

Alternative splicing in exon 9 of glucocorticoid receptor pre-mRNA is regulated by SRp40 - Xue-Bo Yan; Chen-Hong Tang; Yan Huang; Hui Fang; Zhi-Qiang Yu; Li-Min Wu; Rong-Yu Liu (Molecular Biology Reports, 2010)

Sequencing of Part of the Goat agouti Gene and SNP Identification - Xiang-long Li; Jing-wen Zhao; Chun-juan Tang; Rong-yan Zhou; Guiru Zheng; Lan-hui Li; Xiu-li Guo (Biochemical Genetics, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Molecular characterization of global maize breeding germplasm based on genome-wide single nucleotide polymorphisms - Yanli Lu; Jianbing Yan; Claudia T. Guimarães; Suketoshi Taba; Zhuanfang Hao; Shibin Gao; Shaojiang Chen; Jiansheng Li; Shihuang Zhang; Bindiganavile S. Vivek; Cosmos Magorokosho; Stephen Mugo; et al. (Theoretical and Applied Genetics, 2009)

Erratum to: Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2009)

Isolation and Evolution Mode Analysis of NBS–LRR Resistance Gene Analogs from Hexaploid Wheat - De-Shun Feng; Yan Li; Hong-Gang Wang; Xing-Feng Li; Ju-Rong Gao (Plant Molecular Biology Reporter, 2009)

Hydraulic pressure inducing renal tubular epithelial-myofibroblast transdifferentiation in vitro - Fei-yan Li; Xi-sheng Xie; Jun-ming Fan; Zi Li; Jiang Wu; Rong Zheng (Journal of Zhejiang University-SCIENCE B, 2009)

Temporal patterns of net soil N mineralization and nitrification through secondary succession in the subtropical forests of eastern China - En-Rong Yan; Xi-Hua Wang; Ming Guo; Qiang Zhong; Wu Zhou; Yong-Fu Li (Plant and Soil, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Preparation and In Vitro Evaluation of Solid Dispersions of Total Flavones of Hippophae rhamnoides L. - Yan Xie; Guowen Li; Xiurong Yuan; Zhenzhen Cai; Rong Rong (AAPS PharmSciTech, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Cloning and functional analysis of wheat V-H+-ATPase subunit genes - Qian Zhao; Yan-Jun Zhao; Bao-Cun Zhao; Rong-Chao Ge; Ming Li; Yin-Zhu Shen; Zhan-Jing Huang (Plant Molecular Biology, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

One-step preparation of antibody and oligonucleotide dual-labeled gold nanoparticle bio-probes and their properties - Xiao-li Kong; Fei-yan Qiao; Hui Qi; Fu-rong Li (Biotechnology Letters, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Systematic biotic responses to palaeoenvironmental change in the Late Pleistocene southern South China Sea: a preliminary study - Muhong Chen; Qianyu Li; Lanlan Zhang; Fan Zheng; Jun Lu; Rong Xiang; Lili Zhang; Wen Yan; Zhong Chen; Shangbin Xiao (Journal of Quaternary Science, 2008)
Oxygen and carbon isotopes from the planktonic foraminifer Globigerinoides sacculifer , trace element contents, calcium carbonate, biogenic silica, grain size, and abundances of diatoms, radiolarians and foraminifera in a deep‐sea core from the southwestern South China Sea were analysed to investigate the response of various marine ecological communities to environmental changes over the last 200 ka. The synthesised results show that the quality of the palaeoecological environment for biological growth is primarily affected by nutrient supply and terrigenous disturbance. Ba and P are important nutrient elements for the growth of diatoms, radiolarians and planktonic foraminifera. Together with dissolved silica and calcium carbonate in sea water, these elements may control microbiotic development. However, variations in Fe content appear to affect diatom and radiolarian abundance. Optimal biotic growth occurs when nutrients are abundant and when there is minimal terrigenous disturbance. Biotic growth decreases when sea water is highly oligotrophic and terrigenous input is high. Maximum biological growth occurred in the mid Holocene, but deteriorated soon afterwards owing to increased terrigenous input, causing a decrease of biological abundance and productivity in the late Holocene. The results also indicate how the Toba volcanic eruption ca. 74 ka ago contributed to changing the ecological environment in the southern South China Sea. Copyright © 2008 John Wiley & Sons, Ltd.

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Effects and complications of placement of motility coupling post in porous polyethylene orbital implants - Hong-guang Cui; Rong-rong Hu; Hui-yan Li; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Phytase expression in transgenic soybeans: stable transformation with a vector-less construct - Xiao Rong Gao; Guo Kun Wang; Qiao Su; Yan Wang; Li Jia An (Biotechnology Letters, 2007)

Knockout of the gene (ste15) encoding a glycosyltransferase and its function in biosynthesis of exopolysaccharide in Streptomyces sp. 139 - Qing-Li Sun; Ling-Yan Wang; Jun-Jie Shan; Rong Jiang; Lian-Hong Guo; Yang Zhang; Ren Zhang; Yuan Li (Archives of Microbiology, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Timing and duration of supergene mineralization at the Xinrong manganese deposit, western Guangdong Province, South China: cryptomelane 40Ar/39Ar dating - Jian-Wei Li; Paulo Vasconcelos; Wei Zhang; Xiao-Dong Deng; Nurdan Duzgoren-Aydin; Dai-Rong Yan; Jian-Qiang Zhang; Ming-An Hu (Mineralium Deposita, 2007)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Effects of predator-mediated apparent competition on the population dynamics of Tetranychus urticae on apples - Chang-zhong Liu; Lin Yan; Hua-rong Li; Gang Wang (BioControl, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)